2011
DOI: 10.1152/ajpendo.00291.2011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic vs. resistance training on visceral and liver fat stores, liver enzymes, and insulin resistance by HOMA in overweight adults from STRRIDE AT/RT

Abstract: While the benefits of exercise are clear, many unresolved issues surround the optimal exercise prescription. Many organizations recommend aerobic training (AT) and resistance training (RT), yet few studies have compared their effects alone or in combination. The purpose of this study, part of Studies Targeting Risk Reduction Interventions Through Defined Exercise-Aerobic Training and/or Resistance Training (STRRIDE/ AT/RT), was to compare the effects of AT, RT, and the full combination (AT/RT) on central ectop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
186
2
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(205 citation statements)
references
References 34 publications
8
186
2
9
Order By: Relevance
“…Further, such brief training would allow an entire session that also includes RT to only require about 45 min. It is important to note that recent studies such as STRRIDE AT/RT [57][58][59], while showing superior effects for long duration AT vs. RT on ectopic fat, may have found (as the authors noted) an effect from caloric expenditure and deficit that in a new multiple health behavior protocol would be produced from PA and quality nutrition without extended AT.…”
Section: Very Brief Aerobic Training To Improve Treatmentmentioning
confidence: 94%
“…Further, such brief training would allow an entire session that also includes RT to only require about 45 min. It is important to note that recent studies such as STRRIDE AT/RT [57][58][59], while showing superior effects for long duration AT vs. RT on ectopic fat, may have found (as the authors noted) an effect from caloric expenditure and deficit that in a new multiple health behavior protocol would be produced from PA and quality nutrition without extended AT.…”
Section: Very Brief Aerobic Training To Improve Treatmentmentioning
confidence: 94%
“…Some studies have reported elevated HDL after endurance training [52]. Many of the participants in the present study used statins, which makes it difficult to interpret data on lipids.…”
Section: Discussionmentioning
confidence: 81%
“…These differences include the use of circuit-based training (which has a concurrent 'aerobic' exercise stimulus) [19,22], the use of home-based prescription [17], and variation in training intensities and study populations, all of which combined limit the ability to generalize findings and draw practical conclusions. The largest study to date which has directly compared aerobic exercise with PRT observed significant reduction in liver fat score (assessed via attenuation of computed tomography) with 8 months of aerobic exercise training but not with PRT in overweight adults [20]. Moreover, despite performing double the training load of the aerobic alone or PRT alone groups, aerobic exercise combined with PRT led to a non-significant reduction in liver fat.…”
Section: Progressive Resistance Trainingmentioning
confidence: 93%
“…To date, there is sparse evidence for the efficacy of PRT as per these guidelines for liver fat reduction. Of the nine studies employing PRT in isolation, five observed a significant reduction in liver fat [5,13,[17][18][19], three of which conformed with the abovementioned guidelines [5,13,18], while four showed no benefit [12,[20][21][22] with discrepancies in outcomes likely due to the large heterogeneity in study design. These differences include the use of circuit-based training (which has a concurrent 'aerobic' exercise stimulus) [19,22], the use of home-based prescription [17], and variation in training intensities and study populations, all of which combined limit the ability to generalize findings and draw practical conclusions.…”
Section: Progressive Resistance Trainingmentioning
confidence: 99%